1994
DOI: 10.1128/jvi.68.7.4525-4537.1994
|View full text |Cite
|
Sign up to set email alerts
|

Bgp2, a new member of the carcinoembryonic antigen-related gene family, encodes an alternative receptor for mouse hepatitis viruses

Abstract: Murine coronaviruses such as mouse hepatitis virus (MHV) infect mouse cells via cellular receptors that are isoforms of biliary glycoprotein (Bgp) of the carcinoembryonic antigen gene family (G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 44 publications
7
131
0
Order By: Relevance
“…Among group II coronaviruses, only the receptor for the murine coronavirus (MHV) is known. MHV enter the cell after binding members of the pleiotropic family of carcinoembryonic antigen-cell adhesion molecules (CEACAMs; CD66a) (Chen et al, 1995(Chen et al, , 1997Dveksler et al, 1993;Nedellec et al, 1994). CEACAMs are glycoproteins possessing two or four immunoglobulin-like extracellular domains followed by a transmembrane domain and a cytoplasmic tail (Nedellec et al, 1994).…”
Section: Coronaviruses and The Outbreak Of Sarsmentioning
confidence: 99%
“…Among group II coronaviruses, only the receptor for the murine coronavirus (MHV) is known. MHV enter the cell after binding members of the pleiotropic family of carcinoembryonic antigen-cell adhesion molecules (CEACAMs; CD66a) (Chen et al, 1995(Chen et al, , 1997Dveksler et al, 1993;Nedellec et al, 1994). CEACAMs are glycoproteins possessing two or four immunoglobulin-like extracellular domains followed by a transmembrane domain and a cytoplasmic tail (Nedellec et al, 1994).…”
Section: Coronaviruses and The Outbreak Of Sarsmentioning
confidence: 99%
“…The HE proteins of group 2 coronaviruses interact either with Neu4,5Ac 2 or sialic acids with O-acetylation at position 9 (Neu5,9Ac 2 ). While human coronaviruses related to the reference strain HCoV OC43 and BCoV specifically interact with Neu5,9Ac 2 via the HE [13,14] and the spike glycoprotein [15], the murine coronavirus strains S and JHM recognize Neu4,5Ac 2 [9] and a cellular glycoprotein termed MHV-receptor or CEACAM 1a [16][17][18][19]. For Influenza C viruses and BCoV it was shown that they utilize Neu5,9Ac 2 as receptor determinant, which may be part of glycoproteins or the sialic-acid-containing gangliosides [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several different proteins work as MHV receptors (Chen et al, 1995;Dveksler et al, 1991;Nedellec et al, 1994;Yokomori and Lai, 1992), among which CEACAM1 is the most functional receptor. Two allelic forms are known for CEACAM1, CEACAM1a (MHVR1) and CEACAM1b (MHVR2) (Beauchemin et al, 1999;Dveksler et al, 1993;Yokomori and Lai, 1992).…”
Section: Introductionmentioning
confidence: 99%